Penerapan Pencatatan Keuangan Secara Digital Pada UMKM Bata Press UD.Intan Desa Pejaten Kabupaten Tabanan - Agus Putra Mardika; I Putu Dharmawan Suryagita Susila Putra; I Gede Bayu Wirayudha (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The application of digital financial records is very important for SMEs in the industrial era 4.0. Therefore, SMEs need to implement digital financial records to make it easier to make financial reports. SMEs, namely UD. Intan is a business engaged in the manufacture of batapress. UD. Intan is located in Kediri District, Tabanan Regency. The results of observations made that the recording of the financial statements of UD. Intan Manually and the recording is done in a simple way that only records income and expenses. Based on the results of these observations, the researchers applied training and mentoring strategies for SMEs at UD. Intan. Goals training and assistance to SMEs UD. Intan is to introduce digital financial records that will facilitate the preparation of financial reports. From the results of this study, a solution emerged, namely the use of digital financial records to make it easier to make various financial reports.